The problem of enforcing court judgments on jointly owned assets between the debtor and a third party in the Saudi enforcement system: A comparative study - Atheer Saad Al-Zahrani; Al-Hanouf Abdulaziz Al-Sulami (International Journal of Law Research and Studies, 2026)
This research aims to conduct a comparative study with relevant Arab and international legal systems as a means of exploring different experiences and legislative approaches that can be utilized in developing the Saudi legal system. The research demonstrated that the issue of determining the debtor’s share in jointly owned property is the primary source of most practical problems, and that ambiguity in records or the continuation of joint ownership without effective division weakens the general guarantee and hinders enforcement. It also revealed that the enforcement judge plays a pivotal role in protecting the balance between the creditor’s rights and the rights of the partners, through their authority to allocate the property subject to enforcement, suspend or continue proceedings, appoint a guardian or liquidator, and accept provisional and substantive objections. The comparison with the Egyptian, Jordanian, and Emirati legal systems showed a general Arab trend toward restricting enforcement to the amount of the debt and providing practical solutions to protect jointly owned housing and prevent fragmentation of ownership in a way that diminishes its economic value or harms the partners. The research showed that the digital transformation in enforcement procedures (Najiz platforms, Mazad, and the like) contributed to accelerating reservation and forced sale and raising the level of transparency, but in return it requires continuous updating of technical and judicial controls so that speed does not turn into a source of new grievances.